Case study of the Beijing 2022 Olympic Winter Games: Implications for global mass gathering events amidst the COVID-19 pandemic - Huo, Da; Shen, Ying; Zhou, Tao; Yu, Tong; Lyu, Ruoran; Tong, Ying; Gao, Ting; Wang, Quanyi (Frontiers in Public Health, 2023)
Objective This study aimed to evaluate the public health countermeasures against coronavirus disease 2019 (COVID-19) that are important for organizing mass gathering events (MGEs) during a pandemic and to identify the practices suitable for application at future MGEs. Methods This study analyzed data from the Beijing 2022 Olympic Winter Games. The aforementioned analysis was conducted from the viewpoints of overseas stakeholders and Chinese residents. The comprehensive set of countermeasures established to prevent the transmission of the COVID-19 pandemic comprised the bubble strategy, the three-layer testing strategy (pre-departure testing, testing at the airport, and daily screening), the mandatory wearing of N95 masks, and mandatory vaccination. Findings A total of 437 positive cases within the bubble were reported during the Games, of which 60.6% were detected through screening at the airport and 39.4% were detected through routine screening. Nearly, 92.0% of the positive cases were detected within 7 days of arrival in China, and 80.8% of the cases had already been identified before the Opening Ceremony of the Games. Outside the bubble, no Games stakeholders were infected and no spectator contracted COVID-19. The bubble strategy, the three-layer testing strategy, the mandatory wearing of N95 masks, and mandatory vaccination are promising countermeasures to prevent the transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) during MGEs. Conclusion Public health countermeasures introduced during the Beijing 2022 Olympic Winter Games were proven to be useful. The success in delivering and organizing the Games instills confidence and leaves a public health legacy for future MGEs amid the pandemic of COVID-19 or future emerging infectious diseases.